Rekonstruksi Teori Komunikasi Organisasi dalam Era Digital dan Disrupsi Informasi: Studi Literatur - Heri Wahyudi Marpaung; Hasnun Jauhari Ritonga (CV. Ulil Albab Corp, 2026)
This study aims to: 1) identify the development of organizational communication theory in the context of digitalization and information disruption; 2) analyze the limitations of classical organizational communication theory in explaining algorithm-based communication and digital platforms; and 3) formulate a framework for reconstructing organizational communication theory that is more adaptive to the digital era. The study uses a qualitative approach with the Systematic Literature Review (SLR) method based on the PRISMA protocol for indexed scientific articles from 2015–2024. The analysis is conducted through a thematic approach to map paradigm shifts and conceptual synthesis in contemporary organizational communication studies. The results show that: 1) Organizational communication theory has undergone a significant transformation from a structural-hierarchical paradigm to a digital-network paradigm; 2) Classical theories such as the linear transmission model and systems theory have limitations because they have not integrated the role of algorithms, digital platforms, and non-human actors in the communication process. In the Digital Ecosystem, the distribution of organizational messages is influenced by algorithmic logic, the attention economy, and the dynamics of online publics that are open and cannot be fully controlled by institutions; and 3) The framework for reconstructing organizational communication theory is based on three main Principles: network communication, Algorithmic Integration, and the Digital Ecosystem perspective. This reconstruction confirms that organizational communication in the digital era is hybrid and interdependent between humans, technology, and platform structures. These findings provide theoretical implications for broadening the scope of organizational communication analysis, as well as practical implications for organizations in managing reputation and communication strategies amidst the complexity of information disruption.